2015
DOI: 10.4088/jcp.14m09587
|View full text |Cite
|
Sign up to set email alerts
|

Association of Obesity and Inflammatory Marker Levels on Treatment Outcome

Abstract: ClinicalTrials.gov identifier: NCT00955955.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Conventional antidepressants (e.g., fluoxetine) have been found to reduce both central and peripheral levels of the pro-inflammatory cytokine interleukin-1 beta (IL-β) in the alleviation of depressive symptoms [ 32 ]. Other treatments with antidepressant properties have also been reported with mechanistically dissimilar treatments (e.g., omega 3 fatty acids, L-methylfolate) [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Conventional antidepressants (e.g., fluoxetine) have been found to reduce both central and peripheral levels of the pro-inflammatory cytokine interleukin-1 beta (IL-β) in the alleviation of depressive symptoms [ 32 ]. Other treatments with antidepressant properties have also been reported with mechanistically dissimilar treatments (e.g., omega 3 fatty acids, L-methylfolate) [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…These include administration of BH4 itself [ 269 ], which is currently approved in a synthetic form to treat phenylketonuria [ 270 - 272 ], and folic acid or S-adenosyl-methionine (SAMe), which have a role in the synthesis and/or regeneration of BH4 [ 3 , 273 , 274 ]. Although effects of BH4 administration on behavioral symptoms have not been reported outside of case reports [ 275 , 276 ], folic acid (in the form of L-methylfolate) and SAMe have demonstrated efficacy as adjuvants in depression trials [ 277 - 281 ]. Administration of L-methylfolate (marketed as Deplin and Zervalx) to patients with MDD has been shown to augment the efficacy of standard antidepressant therapy in two studies [ 278 , 279 ], however mixed results were reported in two parallel-sequential trials with only one trial finding efficacy over placebo [ 280 ].…”
Section: Mechanisms Of Inflammation Affects On Threat and Reward Circmentioning
confidence: 99%
“…DNA hypomethylation can be corrected by methyl donors. l -Methylfolate has been tested as an adjunctive therapy in many clinical trials, 123 , 124 , 125 , 126 , 127 proving to be safe and effective in MDD patients. Another methyl donor, S -adenosyl methionine ((2 S )-2-amino-4-[[(2 S ,3 S ,4 R ,5 R )-5-(6-aminopurin-9-yl)-3,4-dihydroxyoxolan-2-yl]methyl-methylsulfonio]butanoate), has been shown to restore normal gene expression in neuroblastoma cells.…”
Section: Psychosis In Bd As a Shared Traitmentioning
confidence: 99%